Estrogens modulate expression of cathepsin D and actin in a rat model of parkinson's disease - Leiva, Natalia Lorena (2021)
Parkinson´s disease (PD) is a neurodegenerative disorder characterized by the progressive loss of dopaminergic neurons from substantia nigra parscompacta (SNc). A genetic study identified 24 loci that are associated with PD; 11 of them are involved in/or disrupt various functions of theautophagic-lysosomal pathway. Lysosomes participate in the degradation of macromolecules from endocytosis and autophagy processes.Epidemiological and clinical studies reveal a difference in the development of PD between genders, giving sex hormones a neuroprotective functionand making them an interesting therapeutic proposal. The objective of this study is to analyze the effect of estrogens on the expression of lysosomalproteins in a rat model with the PD phenotype. Two-month-old male Sprague-Dawley rats were subjected to stereotaxic surgery to administer 6-hydroxydopamine (6-OHDA) or artificial cerebrospinal fluid (V) to the left striatum. After 7 days, they received chronic treatment for 10 days with17-β-estradiol (E) or V. The groups were made up of C (V lesion); E (V + E injury); HP (6-OHDA injury) and HPE (6-OHDA + E injury). After thetreatments, the animals were sacrificed, and the substantia nigra and prefrontal cortex were extracted and homogenized. Membranous and cytosolicfractions of the prefrontal cortex were obtained by differential centrifugation. The samples were processed for immunoblotting using antibodiesagainst cathepsin D (CatD) and actin. Preliminary results show that chronic treatment with estrogens increases the expression of CatD and actin inthe substantia nigra, and in the prefrontal cortex both proteins are increased in the cytosolic fraction. Since CatD reduces the α-synucleinconcentration in PD, the results suggest that an increase of the lysosomal function would exert neuroprotective action on cells affected by the disease.Likewise, it is worth mentioning that estrogens could also modulate the organization of the cytoskeleton, as a stage in neuromodulation.